Halal Indonesia: creating global nation branding through communication and diplomacy - Widyastuti, Nurprapti Wahyu; Rahesta, Marchela; Wahyuni, Isti Nursih (Jurnal Studi Komunikasi, 2025)
The global demand for halal products is continuing to rise in tandem with the growing trend of the halal lifestyle. Indonesia, with the world's largest Muslim population, aims to become a global halal hub, although it currently ranks fourth in the SGIE 2023 report. This study explored how Indonesia, through the BPJPH (Super body Government Agency for Halal Enforcement), utilised public communication and diplomacy to enhance its nation branding in the global halal industry. Using a qualitative case study approach, data were collected through interviews, website analysis, social media content, and event documentation. Findings indicate that BPJPH promotes halal branding through the SEHATI campaign, bilateral cooperation, and strategic media approaches. These efforts demonstrate the role of public communication and diplomacy in enhancing Indonesia's credibility and visibility in the global halal industry. The study highlights the significance of soft power and multi-stakeholder engagement in supporting Indonesia's goal to lead the global halal economy.